Analysis of Work Discipline Implementation on Employee Work Effectiveness (A Study on The Technician Division of an Automotive Company in Bandung City) - Budiarti, Isniar; Putri, Mega Andira (Universitas Komputer Indonesia, 2025)
This research aims to analyze the effect of work discipline on the effectiveness of technician employees at an automotive company in Bandung City. This research used a sample of 30 technician employees with a saturated sampling technique, where the entire population was sampled. Data collection was carried out through interviews and questionnaires. The analysis method used in this research is simple linear regression analysis, which is then processed using SPSS 20 for Windows software. The research's results indicate that work discipline significantly affected the effectiveness of employee work in the technician division of an automotive company in Bandung City. Thus, it can be concluded that if work discipline increases, work effectiveness will also increase. However, attendance and work procedure compliance still hinder goal achievement and work completion. Therefore, every employee is responsible for improving discipline, especially regarding punctual arrival and compliance with company rules. In addition, better time management and awareness of the importance of following established work procedures will help improve overall work effectiveness in the automotive company technician division in Bandung City. This research can contribute to improving employee discipline policies, increasing work effectiveness, and optimizing company productivity by emphasizing the importance of attendance, compliance with work procedures, and responsibility among employees